Effect of sulfuric acid pretreatment on breaking hard seed dormancy in diverse accessions of five wild Vigna species - Wang, Y.R.; Hanson, Jean; Mariam, Y.W. (2007)
Many Vigna species are important in agriculture, but a high content of hard seeds usually present which create the difficulties in seed testing and sowing. The effectiveness of the pretreatment periods (0, 3, 6, 9, 12 and 15 min.) for breaking dormancy of hard seeds using concentrated sulfuric acid was investigated for 18 seed lots of 14 accessions of 5 wild Vigna species (V. membranacea, V. oblongifolia, V. racemosa, V. schimperi and V. vexillata). Most pretreatments significantly (P < 0.05) reduced hard seed content and improved germination percentage and germination rate when compared to untreated seeds. Effectiveness of the pretreatment improved as the pretreatment period increased from 3 to 15 min for all samples. The 15 min pretreatment reduced hard seed from 53 to 2% and increased germination from 36% to 85% on average for all samples. This same pretreatment also reached germination to 64% and 79% after 2 and 4 days incubation respectively, compared to 3% and 10% for untreated seeds. The seed imbibition percentage at 24 hour correlated significantly (at 1% level) with the final germination percentage at 14 days for each species.